Ethical consideration of wildlife research in Bangladesh - Pingki, Maria Tabasoom; Hossain, Md Sakhawat; Hasan, Mahmudul; Bilasi, S N; Rahman, Mohammad Matiur (Bangladesh Journal of Zoology, 2026)
In Bangladesh, Wildlife research is essential to biodiversity protection, ecological surveillance, and sustainable resource management. It does, however, bring up important ethical issues, such as cultural sensitivity, legal compliance, human-wildlife relationships, and animal welfare. This study investigates the current ethical frameworks governing wildlife research in Bangladesh, assesses the main obstacles faced by field researchers, and analyses the extent to which international ethical standards have been incorporated into local practices. Risk of habitat destruction, ethical ramifications of capturing, tagging, and handling wild animals, and possible confrontations with indigenous groups and stakeholders are all highlighted and discussed. The review also examines current laws and regulations, institutional review procedures, and the role of national and international guidelines in guaranteeing ethical research practices. Critical evaluations are conducted of research gaps, ethical oversight inconsistencies, and the necessity of context-specific protocols. The review concludes with a list of recommendations for improving ethical governance in wildlife research, which include community involvement, ethics training, capacity building, and the creation of a national ethical framework for wildlife research that is adapted to the socioecological context of Bangladesh. Bangladesh J. Zool. 53(3): 389-410, 2025